THE ROLE OF THE DENTIST IN THE EARLY DIAGNOSIS OF COVID-19 (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Viral infections of the oral cavity are the reason for the frequent visits of patients to the dentist due to damage to the mucous membrane. A group of herpes viruses (herpes simplex 1–8), human immunodeficiency virus (HIV) are capable of infecting and multiplying in the mucous membrane of the human oral cavity. Also, the oral cavity as a point of entry into the body played a decisive role in the pathogenesis of SARS-CoV-2 infection, which caused the global outbreak of coronavirus disease 2019 (COVID-19) and became an active focus of infection and an important reservoir of SARS-CoV-2.